Choice of the equipment of fire hydrants for the internal fire-prevention water pipe - Petukhova Е.А.; Gornostal’ С.А.; Shapovalova Е.А. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The computer program which effectively allows to choose the devices for equipment of fire hydrants and to place fire hydrants in the plan of a building is offered.